Avaliação da existência de isolamento reprodutivo entre duas espécies de veados cinza (Mazama gouazoubira E Mazama nemorivaga) por meio de machos híbridos - Martins, Gabriela Siqueira [UNESP] (2015)
The brown brocket deer (Mazamagouazoubira) and the amazonian brown brocket deer (Mazamanemorivaga) have similar morphological features and parapatric distribution, which questioned thetaxonomic classification of M. nemorivagaas a species for many years. Cytogenetic and morphometric studies suggest M. nemorivaga as a valid species but in most species concepts currently accepted is implicit the idea that two species should not only be genetically distinct, but reproductively isolated. This study evaluated the presence of post zygotic reproductive isolation between M. gouazoubira and M. nemorivaga to elucidate the taxonomic classification of the latter. To this end, seminal characteristics, testicular histology and profiles of testosterone of six animals, intra and interespecificbreeding products were evaluated: three pure M. gouazoubira (PG), a pure M. nemorivaga (PN) and two hybrids (H). Throughout the study testicular and seminal material of two pure animals (one M. gouazoubira and one M. nemorivaga) were added in the analyzes. The results show that five of the six purebreds analyzed (PG1, PG2, PG4, PN1 and PN2) performed well in reproductive analysis, fitting the parameters observed for their respective species. The hybrid H1 was completely sterile while H2 showed severe subfertility, parameters directlyrelated with a low secretion of testosterone and testicular hypoplasia. It is believed that the difference of reproductive parameters between the hybridswas directly related to the sex of their parents. The PG3 animal showed bad reproductive potential, probably linked to a birth defect not elucidated. Based on these data it is possible to suggest the existence of reproductive isolation between M. gouazoubira and M. nemorivaga reinforcing the need for revision of these groups to define their taxonomic position